Barriers to Delivery of Enteral Nutrition in Intensive Care Settings in Saudi Arabia: A Comparative Study of the Perceptions of Health Care Providers Working in Adult and Paediatric ICUs - Zaher S (Dove Medical Press, 2022)
Sara Zaher1,2 1Clinical Nutrition Department, Faculty of Applied Medical Sciences, Taibah University, Madinah, Kingdom of Saudi Arabia; 2National Nutrition Committee (NNC), Saudi Food and Drug Authority (Saudi FDA), Riyadh, Saudi ArabiaCorrespondence: Sara Zaher, Clinical Nutrition Department, Faculty of Applied Medical Sciences, Taibah University, P.O. Box 344, Madinah, 42353, Kingdom of Saudi Arabia, Email Sz332@cam.ac.uk; szaher@taibahu.edu.saBackground and Aims: Achieving optimal nutrition prescription is challenging in critically ill patients. Many factors can hinder the adequate delivery of enteral nutrition (EN) in intensive care units (ICUs). In this study, we aim to describe EN barriers and compare the perceptions of health care practitioners working in adult and paediatric ICUs regarding these barriers.Methods: In this cross-sectional study, data were collected via online survey. All physicians, dietitians, and nurses working in adult or paediatric ICUs across Saudi Arabia were eligible to participate. The survey contained 24 potential EN barriers and participants were asked to rate their importance on a scale from 1 to 5. A total Likert rating score of the 24 items was later calculated.Results: We recruited 244 health care providers working in adult and paediatric ICUs. The most important perceived barriers were "Delay in physician ordering EN initiation" (3.33 ± 1.32), and 'Waiting for dietitians to assess patients' (3.22 ± 1.20). There was a statistical difference between the responses of health care providers based on their work settings for the following items; "Nurses failing to progress feeds according to feeding protocol" (p=0.006) and 'Feeding being held too far prior procedures or operating-room visits' (p=0.021). Profession significantly influenced the total Likert rating score of the 24 items (r=− 0.234, p=0.001).Conclusion: This study identified some barriers of EN delivery in ICUs and showed that participants' perceptions regarding these barriers were influenced by their roles. These findings shed light on the nutritional practices in Saudi hospitals and identify areas of improvement in EN practice and advancements in the field of critical care nutrition in the region.Keywords: enteral nutrition, EN barriers, PICU, ICU